Corpos errantes em movimento e o simulacro da ordem: tramas, trajetos e vivências de “cracudos” nas ruas do Rio de Janeiro - Brandão, Beatriz (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
This article aims to present the scenario of homeless people and crack users in the city of Rio de Janeiro - the so-called "cracudos" - identifying them in an extreme poverty and social relegation process. From sociological concepts opens up lanes anthropological analyzes, as a pre-test field in which they are evaluated the formation of a particular sociability of crack users who live in the city streets. In this way, it is presented a small territorial formation of drug use, calls “cracolândias”, their relationship with the street and their own scales of exclusion as well as the list of users in their own community and the residents of the formal city.
Keywords: Cracudo; Crack; Cracolândia